2016
DOI: 10.1016/j.cjca.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lesion Age on Outcomes of Chronic Total Occlusion Percutaneous Coronary Intervention: Insights From a Contemporary US Multicenter Registry

Abstract: Background We sought to determine the impact of lesion age on procedural techniques and outcomes of chronic total occlusion (CTO) percutaneous coronary intervention (PCI). Methods We examined the characteristics and outcomes of 394 CTO PCIs with data on lesion age, performed between 2012–2016 at 11 experienced US centers. Results Mean patient age was 66 ± 10 years and 85.6% of patients were men. Overall technical and procedural success were 90.1% and 87.5%, respectively. A major adverse cardiovascular even… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 26 publications
1
13
1
Order By: Relevance
“…In contrast to the study of Danek et al , we found that CTO length increased with age of the CTO [10]. In our study, even occlusion duration longer than 6 months was an independent predictor of CTO length over 20 mm.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast to the study of Danek et al , we found that CTO length increased with age of the CTO [10]. In our study, even occlusion duration longer than 6 months was an independent predictor of CTO length over 20 mm.…”
Section: Discussioncontrasting
confidence: 99%
“…As observed in previous studies, patients with longer CTO duration had longer procedure and fluoroscopy time, as well as a greater amount of dye used [10]. These results should be taken into account when planning a procedure with known age of the CTO.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Many studies have shown that the CTO of the coronary artery is associated with cardiac dysfunction 10,11 . Some studies have found that the cardiac function and quality of life can be improved to a certain extent after opening occluded vessels in CTO patients 12‐14 . Many patients with a history of myocardial infarction (MI) underwent at least one coronary artery with CTO and experienced cardiac dysfunction due to failure to timely open the occluded artery 15 .…”
Section: Introductionmentioning
confidence: 99%